ADCP current velocity and CTD measurements at lander stations during HE510 in the German Bight, NOAHC - Robert Kopte; Marius Becker; Peter Holtermann; Christian Winter (PANGAEA, 2022)
Data sets contain profiles of horizontal current velocity, temperature, and salinity collected during R/V Heincke cruise HE510 in May 2018 at two locations in the German Bight: at site NOAHC and site Outer Weser (OW). Current velocities were measured by an uplooking 600 kHz RDI ADCP, which was mounted on the SEDOBS lander. ADCP transducers were located 2.2 m above the seabed. The original ping rate (mode 1) was 0.25 s-1, averaging 4 sub-pings. Data is averaged over 10 min. The cell size is 0.3 m, averaged over 1 m intervals. The vertical reference is extquotesinglemeter above bed extquotesingle (mab). Time is UTC. Each file contains data of one deployment (location), whereas the lander was deployed for at least 1.5 tidal cycles at each location. CTD profiles were taken during part of the lander deployment period from the anchored ship nearby and are exported on the same grid as the ADCP measurements.
In: Kopte, R et al. (2022): ADCP current velocity and CTD measurements at lander stations during HE510 in the German Bight [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.943955